Conditions of nonoscillation of binomial systems of differential equations - Bugir, M. K. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We establish comparison theorems for solutions of the system of Kondrat’ev-type equations y(n)+P(t)y=0.